Islamic Financial Literacy and Financial Management Behavior: The Mediating Effect of Fintech Payments by Female Entrepreneurs at Universities in Madura - Jannatul Rohaini; Budi Achmad Budi Susetyo; Dony Dony Burhan Noor Hasan (RISK : Jurnal Riset Bisnis dan Ekonomi, 2025)
The primary objective of this study is to examine the influence of Islamic financial literacy on the financial management behavior of female entrepreneurs in the Madura region, as well as to evaluate the mediating role of Sharia-based financial payment technology (fintech payment) in this relationship. This research is grounded in the strategic contribution of MSMEs to regional economic development and the persistent challenges encountered by female entrepreneurs in sustaining and growing their businesses, Specifically, this pertains to the limited level of Islamic financial literacy and restricted access to digital financial services that adhere to sharia principlesThis research employs a quantitative approach, utilizing an online questionnaire as the primary survey method for data collection. Respondents were selected purposively, namely Muslim women from academic circles in Madura who have entrepreneurial experience and use sharia fintech payments. The sample size was calculated using the Lemeshow formula, yielding a total of 97 respondents for this study. This was then multiplied by a certain number to become 120 respondents. The data collection process was carried out through a combination of literature review and structured questionnaire distribution, while data analysis was conducted using the SEM-PLS method with SmartPLS 4.0 software. This research is anticipated to contribute meaningfully to the advancement of a digital sharia financial ecosystem that is inclusive, sustainable, and responsive to the specific needs of female entrepreneurs in the Madura region